The Acceptability Among Health Researchers and Clinicians of Social Media to Translate Research Evidence to Clinical Practice: Mixed-Methods Survey and Interview Study - Tunnecliff, Jacqueline; Ilic, Dragan; Morgan, Prue; Keating, Jennifer; Gaida, James E; Clearihan, Lynette; Sadasivan, Sivalal; Davies, David; Ganesh, Shankar; Mohanty, Patitapaban; Weiner, John; Reynolds, John; et al. (JMIR Publications, 2015)
BackgroundEstablishing and promoting connections between health researchers and health professional clinicians may help translate research evidence to clinical practice. Social media may have the capacity to enhance these connections. ObjectiveThe aim of this study was to explore health researchers' and clinicians' current use of social media and their beliefs and attitudes towards the use of social media for communicating research evidence. MethodsThis study used a mixed-methods approach to obtain qualitative and quantitative data. Participation was open to health researchers and clinicians. Data regarding demographic details, current use of social media, and beliefs and attitudes towards the use of social media for professional purposes were obtained through an anonymous Web-based survey. The survey was distributed via email to research centers, educational and clinical institutions, and health professional associations in Australia, India, and Malaysia. Consenting participants were stratified by country and role and selected at random for semistructured telephone interviews to explore themes arising from the survey. ResultsA total of 856 participants completed the questionnaire with 125 participants declining to participate, resulting in a response rate of 87.3%. 69 interviews were conducted with participants from Australia, India, and Malaysia. Social media was used for recreation by 89.2% (749/840) of participants and for professional purposes by 80.0% (682/852) of participants. Significant associations were found between frequency of professional social media use and age, gender, country of residence, and graduate status. Over a quarter (26.9%, 229/852) of participants used social media for obtaining research evidence, and 15.0% (128/852) of participants used social media for disseminating research evidence. Most participants (95.9%, 810/845) felt there was a role for social media in disseminating or obtaining research evidence. Over half of the participants (449/842, 53.3%) felt they had a need for training in the use of social media for professional development. A key barrier to the professional use of social media was concerns regarding trustworthiness of information. ConclusionsA large majority of health researchers and clinicians use social media in recreational and professional contexts. Social media is less frequently used for communication of research evidence. Training in the use of social media for professional development and methods to improve the trustworthiness of information obtained via social media may enhance the utility of social media for communicating research evidence. Future studies should investigate the efficacy of social media in translating research evidence to clinical practice.